“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Impact of aging on the energy efficiency of household refrigerating appliances - Paul, Andreas; Baumhögger, Elmar; Elsner, Andreas; Reineke, Michael; Hueppe, Christian; Stamminger, Rainer; Hoelscher, Heike; Wagner, Hendrik; Gries, Ulrich; Becker, Wolfgang; Vrabec, Jadran (Applied Thermal Engineering)
The parameters required to calculate the energy efficiency of household refrigerating appliances (i.e. refrigerators, freezers and their combinations) are determined by standard measurements. According to regulations, these measurements are carried out when the appliances are new. It is known from previous studies that various technical aging mechanisms can increase electrical energy consumption by up to 36 % over a product lifespan of 18 years. In order to determine the time dependence of the energy consumption of household refrigerating appliances, repeated measurements are carried out in this work. Eleven new appliances are examined under standard measurement conditions. After just two years of operation, an additional energy consumption of up to 11 % is determined. Furthermore, 21 older appliances that had previously been measured in new condition are tested again after up to 21 years of operation. For these older appliances, an average increase of energy consumption of 28 % is found. For individual appliances, the maximum increase is 36 %. An aging model is developed on the basis of these measurement results, which may help to predict the aging-related increase of energy consumption of household refrigerating appliances. This model shows an average increase in energy consumption of 27 % for an appliance age of 16 years. Supplemental performance tests of eight compressors do not show any significant aging effects related to these devices after two years of operation. Furthermore, measurements of the thermal conductivity of aged polyurethane foam test samples are carried out and an increase of its thermal conductivity of 26 % over a period of about three years is determined.
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Numerical analysis of conjugate heat transfer within internally channeled tubes - Al-Lami, Abbas Jarullah Sangoor; Kenig, Eugeny Y.; Inguva, Venkatesh (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Age-related efficiency loss of household refrigeration appliances: Development of an approach to measure the degradation of insulation properties - Hueppe, Christian; Geppert, Jasmin; Stamminger, Rainer; Wagner, Hendrik; Hoelscher, Heike; Vrabec, Jadran; Paul, Andreas; Elsner, Andreas; Becker, Wolfgang; Gries, Ulrich; Freiberger, Alfred (Applied Thermal Engineering)
Despite the omnipresence of household refrigeration appliances, there is still a lack of knowledge about their agerelated efficiency loss over time. Past studies provide basic evidence for increasing electricity consumption of cooling appliances with ageing but fail to investigate the associated technical wear. Concentrating on the degradation of the thermal insulation, we first determined the ageing process of sealed samples of polyurethane rigid foam by investigating changes in cell gas composition and thermal conductivity over time. Simultaneously, the main challenge was to develop an approach that investigates the age-related efficiency loss of the insulation without its destruction. This testing procedure is referred to as the Bonn method. The non-destructive Bonn method was applied to varying refrigerator models in a series of successive experiments to evaluate the insulation degradation over time. Subsequently, the physical relationship between the test value of the Bonn method and the heat transfer through the multi-layered compartment walls of domestic refrigeration appliances was established, ultimately characterising the degrading insulation in terms of increasing heat transfer. Our results give substantiated evidence that the efficiency loss of cooling appliances is greatly influenced by insulation degradation over time. The ageing of sealed samples of polyurethane rigid foam indicates a large initial increase of thermal conductivity by 15% within the first year, corresponding to a change in cell gas composition. These results are in line with those of the Bonn method, emphasising an increasing heat flow through the multi-layered compartment walls of domestic refrigerators with ageing. Therewith, the present study is of significance to a wide range of stakeholders and forms the basis for future research.

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

On the design of heat exchanger equipment for novel-type isobaric expansion engines - Knoke, Torben; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Applied Thermal Engineering)

On the design of heat exchanger equipment for novel-type isobaric expansion engines - Knoke, Torben; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Applied Thermal Engineering)

Heat transfer enhancement in pillow-plate heat exchangers with dimpled surfaces: A numerical study - Piper, M.; Zibart, A.; Djakow, Eugen; Springer, R.; Homberg, W.; Kenig, E.Y. (Applied Thermal Engineering)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Experimental setup of a cascaded two-stage organic Rankine cycle - Dubberke, Frithjof H.; Linnemann, Matthias; Abbas, Wameedh Khider; Baumhögger, Elmar; Priebe, Klaus-Peter; Roedder, Maximilian; Neef, Matthias; Vrabec, Jadran (Applied Thermal Engineering)

Investigation of the structure and spread rate of flames over PMMA slabs - Rakesh Ranga, H.R.; Korobeinichev, O.P.; Harish, A.; Raghavan, Vasudevan; Kumar, A.; Gerasimov, I.E.; Gonchikzhapov, M.B.; Tereshchenko, A.G.; Trubachev, S.A.; Shmakov, A.G. (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Investigation of the structure and spread rate of flames over PMMA slabs - Rakesh Ranga, H.R.; Korobeinichev, O.P.; Harish, A.; Raghavan, Vasudevan; Kumar, A.; Gerasimov, I.E.; Gonchikzhapov, M.B.; Tereshchenko, A.G.; Trubachev, S.A.; Shmakov, A.G. (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Experimental setup of a cascaded two-stage organic Rankine cycle - Dubberke, Frithjof H.; Linnemann, Matthias; Abbas, Wameedh Khider; Baumhögger, Elmar; Priebe, Klaus-Peter; Roedder, Maximilian; Neef, Matthias; Vrabec, Jadran (Applied Thermal Engineering)
Keywords: Industrial and Manufacturing Engineering; Energy Engineering and Power Technology

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)